Economic Security of Russian Economy under the Conditions of Import Substitution Policy Implementation - Andreeva, Natalya Viktorovna; Gromova, Anna Sergeevna; Makasheva, Natalia Petrovna; Vorobeichikov, Sergey Erikovich; Sammer, Aleksandra Borisovna (Economy of Regions, 2015)
In the article, the authors analyze the conditions of import substitution by types of activity from the perspective of the threat to the economic security of Russia. The factors of import substitution are presented. The main factor is the increase of economic and social security by the modernization of Russian economy. Today, a critical measure of the country’s economic security increase is the implementation of import substitution policy. The issue of economic modernization remains of current interest but stays unsolved, especially in the branches where the issue of import substitution is crucial: industry, agriculture, etc. The types of economic activity that can be labeled as open to import substitution are the ones with the high or medium indicators of competitiveness, investment and innovation activity. Within those types, the import substitution policy can be implemented without a threat to economic security. The analysis of the main features of import substitution such as the levels of competitiveness, innovations and investment by the types of economic activity, - is the basis to work out a smart import substitution policy, which will carry no threat to the country’s economic security. The main types of economic activity with the high dependency on import are metallurgical production, chemical industry, wood processing, electrical machines and equipment production, machinery and equipment production, textile manufacture, fishery and fish farming. In the result of the analysis, the following conclusions are drawn: the level of investment for all the types of economic activity presented is critically law; according to the level of innovation and competitiveness, metallurgic production is seen more advantageous on the back of negative dynamics and chemical industry as less advantageous. The other types of activity will face a threat to economic security if the policy of import substitution is implemented without government financing.